Distinct Biological Phenotypes of Marburg and Ravn Virus Infection in Macaques. (12th September 2018) - Nicholas, Veronica V; Rosenke, Rebecca; Feldmann, Friederike; Long, Dan; Thomas, Tina; Scott, Dana P; Feldmann, Heinz; Marzi, Andrea
Abstract: Filoviruses are among the most pathogenic infectious agents known to human, with high destructive potential, as evidenced by the recent Ebola virus epidemic in West Africa. As members of the filovirus family, marburgviruses have caused similar devastating outbreaks, albeit with lower case numbers. In this study we compare the pathogenesis of Ravn virus (RAVV) and Marburg virus (MARV) strains Angola, Musoke, and Ozolin in rhesus and cynomolgus macaques, the 2 nonhuman primate species most commonly used in filovirus research. Our results reveal the most pathogenic MARV strain to be Angola, followed by Musoke, whereas Ozolin is the least pathogenic. We also demonstrate that RAVV is highly pathogenic in cynomolgus macaques but less pathogenic in rhesus macaques. Our results demonstrate a preferential infection of endothelial cells by MARVs; in addition, analysis of tissue samples suggests that lymphocyte and hepatocyte apoptosis might play a role in MARV pathogenicity. This information expands our knowledge about pathogenicity and virulence of marburgviruses.